2014
DOI: 10.3390/nu6125915
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anemia on Child Mortality: An Updated Review

Abstract: Iron deficiency anemia and child mortality are public health problems requiring urgent attention. However, the degree to which iron deficiency anemia contributes to child mortality is unknown. Here, we utilized an exhaustive article search and screening process to identify articles containing both anemia and mortality data for children aged 28 days to 12 years. We then estimated the reduction in risk of mortality associated with a 1-g/dL increase in hemoglobin (Hb). Our meta-analysis of nearly 12,000 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 40 publications
1
121
1
8
Order By: Relevance
“…The most prevalent nutritional disorder is iron deficiency anaemia, with Africa being the most affected region [3] Anaemia can occur at any time and at all stages of the life cycle, with pregnant women and preschool-age children at the greatest risk, making them vulnerable [1]. The prevalence of mild and moderate anaemia may attribute to mortality risk [4]. Anaemia in children is of particular interest since it impairs their mental, physical and social development, causes low immunity, negative behavioural and cognitive effects resulting in poor school performance and work capacity in later life, thereby reducing earning potential and damaging national economic growth in the future [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent nutritional disorder is iron deficiency anaemia, with Africa being the most affected region [3] Anaemia can occur at any time and at all stages of the life cycle, with pregnant women and preschool-age children at the greatest risk, making them vulnerable [1]. The prevalence of mild and moderate anaemia may attribute to mortality risk [4]. Anaemia in children is of particular interest since it impairs their mental, physical and social development, causes low immunity, negative behavioural and cognitive effects resulting in poor school performance and work capacity in later life, thereby reducing earning potential and damaging national economic growth in the future [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Other workers (31,32) have shown that. Hence continued breastfeeding plays a protective role and may possibly reduce the magnitude of poor outcome of anaemia on pregnancy and child survival.…”
Section: (4)mentioning
confidence: 92%
“…Anemia in childhood was defined as a hemoglobin (Hb) concentration below cut off levels established by the World Health Organization: 11 g/dl in children aged 6-59 months, 11.5 g/dl in children aged 5-11 years and 12 g/dl in children 12-14 years old. 7 Biochemical analyses included, serum urea, creatinine (Cr), electrolytes [sodium (Na), potassium (K), calcium (Ca)], aspartate transaminase (AST), alanin aminotransferase (ALT), lactate dehydrogenase (LDH), C-reactive protein (CRP), and B12 vitamin and folate levels. Diagnosis of CD was done when vitamin B12 levels were <148 pmol/L, with normal folate levels, and with exclusion of other causes of anemia.…”
Section: Methodsmentioning
confidence: 99%